2023
DOI: 10.3390/biomedicines11030734
|View full text |Cite
|
Sign up to set email alerts
|

NEK1-Mediated Phosphorylation of YAP1 Is Key to Prostate Cancer Progression

Abstract: The key to preventing mCRPC progression is understanding how androgen-dependent PCa cells progress to independence and modify their transcriptional repertoire accordingly. We recently identified a novel axis of the Hippo pathway characterized by the sequential kinase cascade induced by androgen deprivation, AR−>TLK1B>NEK1>pYAP1-Y407, leading to CRPC adaptation. Phosphorylation of YAP1-Y407 increases upon ADT or induction of DNA damage, correlated with the known increase in NEK1 expression/activity, an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 38 publications
1
13
0
Order By: Relevance
“…TLK1 may regulate the Hippo pathway through its activity on NEK1. We showed that overexpression of the NEK1-T141A mutant results in reduced levels of YAP, along with evidence of an elevated cleaved product (Cl-YAP) [100,103]. Decreased YAP levels and Cl-YAP are also seen in control LNCaP cells treated with 1µM THD for 1h (+/-BIC), with similar effects obtained with J54 (our in-house, test, 2 nd generation TLK1 inhibitor, described later).…”
Section: Tlk1 In Pca Progressionsupporting
confidence: 69%
See 2 more Smart Citations
“…TLK1 may regulate the Hippo pathway through its activity on NEK1. We showed that overexpression of the NEK1-T141A mutant results in reduced levels of YAP, along with evidence of an elevated cleaved product (Cl-YAP) [100,103]. Decreased YAP levels and Cl-YAP are also seen in control LNCaP cells treated with 1µM THD for 1h (+/-BIC), with similar effects obtained with J54 (our in-house, test, 2 nd generation TLK1 inhibitor, described later).…”
Section: Tlk1 In Pca Progressionsupporting
confidence: 69%
“…However, the fundamental mechanism of YAP hyperactivation in PCa onset and development remains elusive. Importantly, our preliminary studies discovered that TLK1 has a role in the Hippo pathway (via NEK1mediated upregulation of YAP) and can directly hasten the conversion toward CRPC [100]. Experimentally, we found that 2-fold overexpression of wt-NEK1 (but not the T141A mutant) hastens the progression of LNCaP cells to AI growth [78].…”
Section: Tlk1 In Pca Progressionmentioning
confidence: 76%
See 1 more Smart Citation
“…As for the NEK1 function in cancer, several publications reported overexpression of NEK1 in renal cell carcinoma [57] and gliomas [58]. NEK1 may play an oncogenic function in prostate cancer [59,60] through the phosphorylation of YAP [61]. In our analyses of available databases, we found that gene expression of NEK1 is downregulated in EAC compared to normal samples in TCGA and two GEO datasets (GSE13898 and GSE74553).…”
Section: Discussionmentioning
confidence: 66%
“…These include highly recurrent AR mutations and TMPRSS2-ERG gene fusions [ 36 , 45 , 46 , 47 ]. It is worth noting that these TMPRSS2-ERG gene rearrangements activate the transcriptional program regulated by YAP1 and that prostate-specific activation of either ERG or YAP1 in mice induces similar transcriptional changes and results in age-related prostate tumors [ 24 , 48 , 49 ]. These findings further emphasize the significance of targeting the TLK1-NEK1-YAP pathway during early adaptation to ADT.…”
Section: Clinical Signs Of Ar-negative Diseasementioning
confidence: 99%